Al-Zahiriyyah di Adalusia: Analisis dari Perspektif Pemikiran Islam - Wan Ali, Wan Zailan Kamaruddin (Jurnal Usuluddin, 2009)
This article as the title indicates is to examine the development of al-Zahiriyyah from the very beginning, its thinkers and influenced figures and their thoughts on ‘Ilm Kalam, its impact and influence towards Islam and also Muslim in Andalusia.